Anthropology now and next : essays in honor of Ulf Hannerz - Edited by THomas Hylland Eriksen; Garsten, Christina (ed.); Randeria, Shalini (ed.) (New york Berghahn, 2015)
The scholarship of Ulf Hannerz is characterized by its extraordinary breadth and visionary nature. He has contributed to the understanding of urban life and transnational networks, and the role of media, paradoxes of identity and new forms of community, suggesting to see culture in terms of flows rather than as bounded entities. Contributions honor Hannerz$1 (Blegacy by addressing theoretical, epistemological, ethical and methodological challenges facing anthropological inquiry on topics from cultural diversity policies in Europe to transnational networks in Yemen, and from pottery and literature to multinational corporations.s
Keywords: Anthropology; Cultural Studies